Students’ pro-environmental behavior and environmental learning outcomes based on green consumerism - Ilmi Zajuli Ichsan; Diana Vivanti Sigit; Mieke Miarsyah; Eka Putri Azrai; Erna Heryanti (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
Green consumerism has been considered as one of promising movement in maintaining the environmental quality. This research aimed to describe the students’ pro-environmental behavior (PEB) as considerable as there learning outcome based on green consumerism. This survey research was conducted in State Junior High School 1 of South Tambun, Bekasi, West Java on July-August 2018. The sampling technique used was simple random sampling with 256 students. The subject was divided into two groups: 128 students from seventh grade who had not received environmental learning materials and 128 students from eighth grade who had received environmental learning materials. The data analysis used in this study was an independent t-test. The results of the t-test showed that there was no significant difference of PEB achievement between the two groups. In addition, not with standing that the average of the students’ environmental learning outcomes was 72.76, but there was as high as 78.60% of students’ achievement was classified below the standard value. Thus, teachers should evaluate the environmental materials used. It is expected that Biology subjects on environmental material can accommodate green consumerism concepts.